Calcination-based ceramic fiber and aerogel composite material and preparation process thereof

By doping rare earth elements into ceramic fibers and aerogel composites and forming a SiO2 wrapping layer, the problem of poor thermal insulation of composites is solved, and its thermal insulation and mechanical properties are significantly improved.

CN119430904APending Publication Date: 2025-02-14吉祥三宝高科新材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411741938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Poor thermal insulation of ceramic fibers and aerogel composites leads to poor performance.

Method used

By doping rare earth elements into hydroxyapatite and using the replacement reaction of ethyl orthosilicate and gel precursor, chemical bonds of Si-O-Ca and Si-O-rare earth elements are generated to form SiO2 encapsulation layer, which improves the Thermal insulation properties of composite materials.

Benefits of technology

Improves the uniformity and mechanical properties of composite materials, reduces thermal conductivity, and improves thermal insulation and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162777780000061
    Figure BDA0005162777780000061
  • Figure BDA0005162777780000071
    Figure BDA0005162777780000071
Patent Text Reader

Abstract

The invention discloses a ceramic fiber and aerogel composite material based on calcination and a preparation process thereof, and belongs to the technical field of aerogel composite materials. The preparation process of the ceramic fiber and aerogel composite material comprises the following steps: S1, dispersing hydroxyapatite, rare earth element nitrate and nitric acid in an ethanol water solution, stirring for 0.5-1 hour to obtain a dispersion liquid, adding polyvinylpyrrolidone and N, N-dimethylformamide into the dispersion liquid, and stirring for 2-3 hours to obtain a mixture; s2, after epoxypropane is added into the mixture, standing, aging and soaking are conducted, and a gel precursor is obtained; s3, putting the gel precursor into an ethanol solution of tetraethoxysilane, aging, soaking, drying, calcining and cooling to obtain the ceramic fiber and aerogel composite material. Tests show that the prepared composite material is good in heat insulation property, high in heat stability, high in mechanical strength and suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel composite materials, and in particular relates to a calcined ceramic fiber and aerogel composite material and a preparation process thereof. Background Art

[0002] Aerogel is a nano-advanced material with a three-dimensional network structure. The medium filled in the spatial network structure of aerogel is air, so it has excellent properties such as extremely low density, low thermal conductivity, and high porosity. It has very broad application prospects in the fields of thermal insulation, energy saving and consumption reduction. Ceramic fiber has excellent fire resistance and is widely used in the field of fire prevention. Ceramic fiber aerogel composite material has both the good fire resistance of ceramic fiber and the thermal insulation performance of aerogel. It is a high-performance fireproof and heat-insulating composite material.

[0003] The patent application with the publication number CN 112321313 A discloses a method for reducing the production cost of the traditional impregnation or spraying process and solving the problem of uneven composite of the existing ceramic fiber aerogel felt powder. The ceramic fiber aerogel felt is mainly composed of ceramic fiber and aerogel powder. When preparing the ceramic fiber mixed slurry, aerogel powder is added for synchronous modification, or aerogel powder that has been surface-modified at high temperature is directly added, and then dried at high temperature. The prepared ceramic fiber aerogel felt has the problem of uneven dispersion of ceramic fiber and aerogel powder, resulting in poor performance of ceramic fiber aerogel composite materials. In view of the rapid development of aerogel materials and the limitations of aerogels such as high brittleness, poor wear resistance and thermal insulation, it is urgent to propose an aerogel fiber material with novel structure and performance, a preparation method and application, so as to achieve the purpose of simple production process, short cycle and low cost, give full play to the characteristics and structural advantages of aerogel materials, and further develop and apply aerogels. Summary of the invention

[0004] The object of the present invention is to provide a calcined ceramic fiber and aerogel composite material and a preparation process thereof, so as to solve the problem of poor thermal insulation of the ceramic fiber and aerogel composite material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A preparation process of a calcined ceramic fiber and aerogel composite material comprises the following steps:

[0007] S1. Dispersing hydroxyapatite, rare earth element nitrate and nitric acid in an ethanol aqueous solution, stirring for 0.5-1h to obtain a dispersion, adding polyvinyl pyrrolidone and NN dimethylformamide to the dispersion, stirring for 2-3h to obtain a mixture;

[0008] S2, adding propylene oxide to the mixture, allowing it to stand for aging and soaking to obtain a gel precursor;

[0009] S3. Placing the gel precursor in an ethanol solution of ethyl orthosilicate, aging, soaking, drying, calcining, and cooling to obtain a ceramic fiber and aerogel composite material.

[0010] Furthermore, the particle size of the hydroxyapatite is 20-40 mesh.

[0011] Furthermore, the nitric acid is concentrated nitric acid with a mass fraction of 60-70wt%; the mass fraction of ethanol in the ethanol aqueous solution is 50%-60%; the mass fraction of ethyl orthosilicate in the ethyl orthosilicate ethanol solution is 20%-30%.

[0012] Furthermore, the rare earth element nitrate is one or a combination of cerium nitrate, yttrium nitrate, lanthanum nitrate, scandium nitrate, and ytterbium nitrate.

[0013] Furthermore, the dosage ratio of the hydroxyapatite, rare earth element nitrate, nitric acid, ethanol aqueous solution, polyvinyl pyrrolidone, NN dimethylformamide and propylene oxide is (2-3) g: (0.1-0.2) g: (15-20) mL: (30-40) mL: (0.01-0.1) g: (5-10) mL: (30-40) mL.

[0014] Furthermore, the usage ratio of the gel precursor and the ethanol solution of tetraethyl orthosilicate is (2-3) g: (30-40) mL.

[0015] Furthermore, the aging is aging at 55-65° C. for 3-5 days; the soaking is soaking in anhydrous ethanol for three times; and the drying is drying at 55-65° C. for 22-24 hours.

[0016] Furthermore, the calcination is carried out by heating the material to 1050-1150° C. at a heating rate of 5-10° C. / min and calcining the material for 1.5-2.5 hours.

[0017] A calcined ceramic fiber and aerogel composite material is prepared by the preparation process of the ceramic fiber and aerogel composite material.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention provides a ceramic fiber and aerogel composite material, which is prepared by doping rare earth elements into hydroxyapatite. Since the radius of rare earth element ions and calcium ions are similar, the rare earth elements can replace calcium, which limits the formation and growth of grains at high temperatures, inhibits crystallization and stabilizes the crystal phase, thereby improving the uniformity of the composite material and reducing the particle size of the composite material. At the same time, rare earth element doping can also reduce the thermal conductivity of the material, increase the thermal expansion coefficient, and thus improve the thermal insulation, thermal stability and mechanical properties of the composite material.

[0020] (2) The tetraethyl orthosilicate used in the present invention undergoes a replacement reaction with the hydroxyl groups on the surface of the gel precursor to generate Si-O-Ca and Si-O-rare earth element chemical bonds. The tetraethyl orthosilicate itself reacts to generate Si-O-Si bonds. These chemical bonds are wrapped in the outer layer of hydroxyapatite to form a SiO2 wrapping layer, thereby improving the thermal insulation performance of the composite material.

[0021] (3) The preparation process of the ceramic fiber and aerogel composite material provided by the present invention is simple, the ceramic fiber and aerogel are evenly distributed, the consistency is good, and it is suitable for large-scale production. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] This embodiment provides a calcined ceramic fiber and aerogel composite material, which is prepared by the following steps:

[0025] S1. Disperse 2.5 g of hydroxyapatite with a particle size of 20 mesh, 0.15 g of cerium nitrate and 20 mL of concentrated nitric acid with a mass fraction of 68 wt% in 40 mL of 50% ethanol aqueous solution, stir for 0.5 h to obtain a dispersion, add 0.05 g of polyvinyl pyrrolidone and 8 mL of N-N-dimethylformamide to the dispersion, stir for 2 h to obtain a mixture;

[0026] S2, after adding 35 mL of propylene oxide to the mixture, aging at 60°C for 3 days, and soaking in anhydrous ethanol three times to obtain a gel precursor;

[0027] S3. Place 2.5 g of the gel precursor in 35 mL of 25% ethyl orthosilicate ethanol solution, age at 60°C for 4 days, soak in anhydrous ethanol three times, dry at 60°C for 24 hours, heat to 1100°C at a heating rate of 5°C / min and calcine for 2 hours, and cool to room temperature to obtain a ceramic fiber and aerogel composite material.

[0028] Example 2

[0029] The present embodiment is different from the embodiment 1 in that the “2.5 g hydroxyapatite of 20 mesh” in S1 is changed into “2.5 g hydroxyapatite of 40 mesh”.

[0030] The remaining raw materials and preparation process remain the same as in Example 1.

[0031] Example 3

[0032] The present embodiment is different from the embodiment 1 in that the "cerium nitrate" in S1 is changed to "yttrium nitrate".

[0033] The remaining raw materials and preparation process remain the same as in Example 1.

[0034] Example 4

[0035] The present embodiment is different from the embodiment 1 in that "2.5 g hydroxyapatite" in S1 is changed to "3 g hydroxyapatite".

[0036] The remaining raw materials and preparation process remain the same as in Example 1.

[0037] Example 5

[0038] The difference between this embodiment and embodiment 1 is that "2.5 g hydroxyapatite" in S1 is changed to "2 g hydroxyapatite".

[0039] The remaining raw materials and preparation process remain the same as in Example 1.

[0040] Example 6

[0041] The present embodiment is different from the embodiment 1 in that the step "2.5 g of gel precursor is placed in 35 mL of 25% by mass ethyl orthosilicate ethanol solution" in S3 is changed to "2 g of gel precursor is placed in 40 mL of 25% by mass ethyl orthosilicate ethanol solution".

[0042] The remaining raw materials and preparation process remain the same as in Example 1.

[0043] Example 7

[0044] The present embodiment is different from the embodiment 1 in that the step "2.5 g of gel precursor is placed in 35 mL of 25% by mass ethyl orthosilicate ethanol solution" in S3 is changed to "3 g of gel precursor is placed in 30 mL of 25% by mass ethyl orthosilicate ethanol solution".

[0045] The remaining raw materials and preparation process remain the same as in Example 1.

[0046] Comparative Example 1

[0047] Compared with Example 1, the difference between this comparative example is that no rare earth element nitrate is added to S1, and the specific implementation steps are as follows:

[0048] S1. Disperse 2.5 g of hydroxyapatite with a particle size of 20 mesh and 20 mL of concentrated nitric acid with a mass fraction of 68 wt% in 40 mL of 50% ethanol aqueous solution, stir for 0.5 h to obtain a dispersion, add 0.05 g of polyvinyl pyrrolidone and 8 mL of N-N-dimethylformamide to the dispersion, stir for 2 h to obtain a mixture;

[0049] The remaining raw materials and preparation process remain the same as in Example 1.

[0050] Comparative Example 2

[0051] Compared with Example 1, this comparative example differs in that no tetraethyl orthosilicate is added to S3, and the specific implementation steps are as follows:

[0052] S3. Place 2.5 g of the gel precursor in 35 mL of anhydrous ethanol, age at 60 °C for 4 days, soak in anhydrous ethanol three times, dry at 60 °C for 24 hours, heat to 1100 °C at a heating rate of 5 °C / min and calcine for 2 hours, and cool to room temperature to obtain a ceramic fiber and aerogel composite material.

[0053] The remaining raw materials and preparation process remain the same as in Example 1.

[0054] Comparative Example 3

[0055] Compared with Example 1, the difference between this comparative example is that rare earth element nitrate and tetraethyl orthosilicate are not added at the same time, and the specific implementation steps are as follows:

[0056] S1. Disperse 2.5 g of hydroxyapatite with a particle size of 20 mesh and 20 mL of concentrated nitric acid with a mass fraction of 68 wt% in 40 mL of 50% ethanol aqueous solution, stir for 0.5 h to obtain a dispersion, add 0.05 g of polyvinyl pyrrolidone and 8 mL of N-N-dimethylformamide to the dispersion, stir for 2 h to obtain a mixture;

[0057] S2, after adding 35 mL of propylene oxide to the mixture, aging at 60°C for 3 days, and soaking in anhydrous ethanol three times to obtain a gel precursor;

[0058] S3. Place 2.5 g of the gel precursor in 35 mL of anhydrous ethanol, age at 60 °C for 4 days, soak in anhydrous ethanol three times, dry at 60 °C for 24 hours, heat to 1100 °C at a heating rate of 5 °C / min and calcine for 2 hours, and cool to room temperature to obtain a ceramic fiber and aerogel composite material.

[0059] The remaining raw materials and preparation process remain the same as in Example 1.

[0060] Comparative Example 4

[0061] The difference between this comparative example and Example 1 is that the calcination time in S3 is extended to 4 h.

[0062] The remaining raw materials and preparation process remain the same as in Example 1.

[0063] The performance of the ceramic fiber and aerogel composite materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was tested.

[0064] The results are shown in Table 1:

[0065] Table 1

[0066]

[0067]

[0068] It can be seen from Table 1 that the only difference between Examples 2-7 and Example 1 is that the raw materials or raw material ratios in the preparation process are changed within a reasonable range. From the results, ceramic fiber and aerogel composite materials with low thermal conductivity and excellent mechanical properties can be obtained.

[0069] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is whether rare earth nitrate is added. Rare earth element doping can not only reduce the thermal conductivity of the material, increase the thermal expansion coefficient, and thus improve the performance of the composite material, but also replace calcium, limit the formation and growth of grains at high temperature, and can inhibit crystallization and stabilize the crystalline phase, thereby improving the uniformity of the composite material. Therefore, the results of Comparative Example 1 show a decrease in thermal conductivity and shrinkage. Compared with Example 1, Comparative Example 2 cannot form a layer of SiO2 wrapping on the outer layer of hydroxyapatite without adding tetraethyl orthosilicate, resulting in reduced thermal insulation and mechanical strength. Compared with Comparative Examples 1-2 and Example 1, Comparative Example 3 has a more severe decrease in thermal conductivity, shrinkage and compressive strength, reflecting that rare earth nitrate and tetraethyl orthosilicate play a synergistic role in the composite material; Compared with Example 1, after the calcination time is increased, the compressive strength of the composite material is improved, but its thermal conductivity is also improved accordingly. In practical applications, it is necessary to balance the two and adjust them to the required preparation conditions.

[0070] In summary, the present invention provides a preparation process for a ceramic fiber and aerogel composite material. The prepared ceramic fiber and aerogel composite material has good thermal insulation, strong thermal stability, high mechanical strength, and a simple and feasible preparation process, which is suitable for large-scale application.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a composite material of calcined ceramic fiber and aerogel, characterized in that: The following steps are involved: S1. Dispersing hydroxyapatite, rare earth element nitrate and nitric acid in an ethanol aqueous solution, stirring for 0.5-1h to obtain a dispersion, adding polyvinyl pyrrolidone and NN dimethylformamide to the dispersion, stirring for 2-3h to obtain a mixture; S2, adding propylene oxide to the mixture, allowing it to stand for aging and soaking to obtain a gel precursor; S3. Placing the gel precursor in an ethanol solution of ethyl orthosilicate, aging, soaking, drying, calcining, and cooling to obtain a ceramic fiber and aerogel composite material.

2. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The particle size of the hydroxyapatite is 20-40 meshes.

3. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The nitric acid is concentrated nitric acid with a mass fraction of 60-70wt%; the mass fraction of ethanol in the ethanol aqueous solution is 50%-60%; the mass fraction of ethyl orthosilicate in the ethyl orthosilicate ethanol solution is 20%-30%.

4. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The rare earth element nitrate is one or a combination of cerium nitrate, yttrium nitrate, lanthanum nitrate, scandium nitrate and ytterbium nitrate.

5. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The dosage ratio of the hydroxyapatite, rare earth element nitrate, nitric acid, ethanol aqueous solution, polyvinyl pyrrolidone, NN dimethylformamide and propylene oxide is (2-3) g: (0.1-0.2) g: (15-20) mL: (30-40) mL: (0.01-0.1) g: (5-10) mL: (30-40) mL.

6. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The usage ratio of the gel precursor and the ethanol solution of tetraethyl orthosilicate is (2-3) g: (30-40) mL.

7. A process for preparing a composite material based on calcined ceramic fiber and aerogel according to claim 1, characterized in that: The aging is carried out at 55-65° C. for 3-5 days; the soaking is carried out for three times with anhydrous ethanol; and the drying is carried out at 55-65° C. for 22-24 hours.

8. The process for preparing a composite material of calcined ceramic fiber and aerogel according to claim 1, characterized in that: The calcination is carried out by heating the temperature to 1050-1150° C. at a heating rate of 5-10° C. / min and calcining for 1.5-2.5 hours.

9. A composite material based on calcined ceramic fiber and aerogel, characterized in that: The ceramic fiber and aerogel composite material is prepared by the preparation process of any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ceramic fiber aerogel composite material and preparation method thereof

    CN112321313A